ChemInform Abstract: Trifluoromethylation of Alkenes by Visible Light Photoredox Catalysis. Issue 19 (18th April 2013) - Iqbal, Naeem; Choi, Sungkyu; Kim, Eunjin; Cho, Eun Jin
Abstract This radical‐based trifluoromethylation of unactivated alkenes shows broad substrate scope and high E‐selectivity.